Synthesis of Enantioenriched Phthalide and Isoindolinone Derivatives from 2-Formylbenzoic Acid - Niedek, Dominik; Schuler, Sören M. M.; Eschmann, Christian; Wende, Raffael C.; Seitz, Alexander; Keul, Felix; Schreiner, Peter R. (Synthesis, 2017)
Transformations of 2-formylbenzoic acid provide direct access to a series of heterocyclic organic compounds such as phthalides and isoindolinones. Here, we use (+)-cinchonine as a catalyst in conjunction with nonafluoro-tert-butanol as a hydrogen-bond donor to afford enantiomerically enriched acylated 3-hydroxyphthalides with up to 99% yield and 90% ee through dynamic kinetic resolution. Moreover, various 3-alkoxyphthalides as well as 2-alkyl-3-hydroxy-1-isoindolinones were synthesized from 2-formylbenzoic acid.
Keywords: acylation; chiral auxiliary; cinchona alkaloids; dynamic kinetic resolution; organocatalysis